POLA KOMUNIKASI ORGANISASI ANTARA PIMPINAN DAN KARYAWAN DI PT. BPR MENTARI TERANG - Bakti, Gideon Bangga; , S.S., M.A., Tsuroyya (The Commercium, 2023)
In today's era, the use of communication patterns that align with the culture and habits of a company will help enhance effectiveness and maximize outcomes. Here, PT. BPR Mentari Terang is a banking company that has high expectations both on a regional and national scale, and has been operating for 20 years. In this study, the researcher will examine the communication patterns utilized by BPR Mentari Terang in running their company, and determine the effectiveness of these communication patterns in achieving maximum results. The researcher employs the phenomenology method with interview data collection techniques. Subsequently, the interview results will be analyzed using Lunenburg's theory on communication patterns. The research findings indicate that PT. BPR Mentari Terang uses a circular communication pattern, which consists of circular, wheel, and Y-pattern communication.